Networking Role of Head Teachers in Addressing Educational Needs of Vulnerable Pupils in Iringa and Mufindi Districts, Tanzania - Joseph, Petrades; Lyamtane, Eugene; Muteti, Catherine (International Journal of Scientific Research and Management (IJSRM), 2025)
This study examined the networking role of public primary school head teachers in addressing the educational needs of vulnerable pupils in Iringa and Mufindi Districts, Tanzania. It was guided by Epstein's theory developed by Joyce Epstein in the late 1980s. The target population consisted 321 schools, 321 head teachers, 642 welfare teachers, and 26,815 vulnerable pupils, with a sample size of 490 selected through a combination of probability and non-probability sampling. Data were collected via questionnaires, interviews, and observations. Quantitative data were analyzed with the aid of SPSS version 27, and descriptive and inferential statistics were obtained. Qualitative data were analyzed through thematic analysis using Turbo Scribe and QDA Miner software. Findings revealed that some schools partnered with organizations such as DREAMS, World Vision Tanzania, UNICEF, TASAF, and Village Community Banks (VICOBA), however, assistance was inconsistent, leaving educational needs of vulnerable pupils unmet. Other schools lacked any organizational connections, resulting in insufficient support for vulnerable pupils. The study concluded that networking diversity among head teachers was crucial for accessing educational support for vulnerable pupils from NGOs, charities and local groups. Head teachers without such connections were urged to establish them to secure resources. The study recommended that head teachers should strengthen networking efforts to engage more educational supporters and collaboration between head teachers and the Ministry of Education Science and Technology to identify vulnerable pupils and develop support mechanisms. Additionally, awareness campaigns to educational stakeholders and training for head teachers on networking strategies were advised to improve access to educational assistance for vulnerable pupils.